Obstacles and strategies for the sustainability of Indonesian small and medium enterprises during Covid-19 Pandemic: A study case at Reban Lestari Farm Kolaka Sulawesi Tenggara - Hastuti Hastuti; Hasnidar Hasnidar; Bustang Bustang (Livestock and Animal Research, 2021)
Objective: This study aimed to assess the sustainability of Indonesian Micro, Small, and Medium Enterprises (MSME) during the Covid-19 pandemic. The specific object of this study was Reban Lestari Farm, an MSME of laying hens farm located in Kolaka, Southeast Sulawesi, Indonesia.Methods: The study composed a qualitative and interpretive approach. Data were collected through interviews and observations, and data were analyzed by using a qualitative descriptive analysis.Results: Results show that the Covid-19 pandemic had significant effects on Indonesian MSMEs, but some MSMEs can survive and even grow despite the pandemic. Laying hens farm was one of the MSMEs that can survive and consistently grow during the Covid-19 pandemic as the commodity still has a high demand amongst consumers.Conclusions: The sustainability of an MSME can still be maintained with multiple business strategies, such as developing innovation and creative thinking to improve product quality and income.